Effects of supplementary light treatment on saffron: integrated physiological, metabolomic, and transcriptome analyses - Li Li; Yujie Zhou; Jingting Wang; Xiwu Qi; Hailing Fang; Yang Bai; Zequn Chen; Xu Yu; Dongmei Liu; Qun Liu; Chengyuan Liang (BMC Plant Biology)
Abstract Background Saffron (Crocus sativus L.) is a perennial, bulbous flower whose stigma is one of the most valuable spices, herbal medicines, and dyes. Light is an essential environmental regulator of plant growth, development, and metabolism. With the popularization of customized light-emitting diode (LED) light sources in facility agriculture, accurate light control has become essential for regulating crop yield and quality. In this study, white, red, and blue LED lights were applied to extend the photoperiod at the start and end of the day during the indoor stage of saffron cultivation. We investigated saffron growth and flowering using non-target metabolomic and transcriptome analyses to determine the flux and accumulation of metabolites from the stigma under different light treatments. Results The results revealed that supplemental red and white lights both promoted dry mass accumulation in the stigma, with the optimal appearance achieved using white light. Supplemental white light promoted saffron flowering, whereas supplemental blue light delayed it. Supplemental blue light promoted crocin-1 and crocin-3 accumulation, whereas supplemental red light promoted crocin-2 accumulation. Expression analysis of key genes and their correlations with crocin-related metabolites may provide useful information for screening functional genes involved in crocin synthesis. Conclusions This study provides useful information for future application of LED light to improve the planting technology, quality, and yield of saffron, and reveals underlying molecular information for the further research.